Aplikasi hukum Islam dalam tatanan masyarakat global di Malaysia dari aspek peradaban umat - Nor, Mohd Roslan Mohd (Fakulti Syari'ah IAIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2010)
This article discusses the development of Islamic law in Malaysia in the context of globalized world. Globalization has posed a challenge to Muslims to provide contemporary world problems with solution. The application of Islamic law is proposed by this paper as one of fundamental ways to overcome this problem. Nevertheless, in the case of Malaysia, the proposed application of Islamic law has resulted in controversy: some groups hail it and the other reject it. In spite of this controversy, the paper describes several aspects of Islamic law that have been successfully implemented in Malaysia such as Islamic Banking and Halal regulation.